Subjective morals - Sapontzis, S. F. (Steve F.) (University Press of America, 2012)
Subjective Morals breaks with tradition to provide a careful analysis of moral values and the goods and evils they produce. Sapontzis explores the subjective and objective bases of moral values and analyzes the concepts and categories that structure our moral practice.